Rancang Bangun Jebakan Tikus Berbasis Internet of Things dan Camera ESP32 - Mohammad Idris Andriansyah; Jamaaluddin Jamaaluddin; A. Ahfas; Izza Anshory; Dwi Hadidjaja (JASEE Journal of Application and Science on Electrical Engineering, 2023)
This research targets rats, which are notorious pests causing food spoilage, disease transmission, and human bites in residential areas, by developing an IoT-based automatic trap. Using ESP32-CAM and IoT technology, the trap ensures effective and safe rat capture with real-time monitoring. The NodeMCU-ESP8266 microcontroller integrates with the Blynk app for seamless control. HCSR-04 Ultrasonic Sensors and 2 Servo Motors detect rats and automate door movement. Employing a research and development approach, the study meticulously assesses sensor, motor, and trap accuracy. Findings highlight the initial Ultrasonic Sensor's proficiency in detecting mice within 16cm, triggering door 1 closure and trapping the mouse. The second Ultrasonic Sensor triggers door 2 to open, releasing the mouse into the electric trap. A Blynk app notification informs users of successful captures. This innovative IoT-based rat trap offers an efficient solution for rodent infestations, potentially enhancing residential environments with scope for further improvements